A Pilot Study to Investigate the Role of Thymidylate Synthase as a Marker of Prognosis for Neoadjuvant Chemotherapy in Gastric and Gastro-Oesophageal Junction Adenocarcinoma. (3rd March 2013) - Mirza, A.; Brown, M.; McNulty, C.; Valentine, J.; Annesley, A.; Galloway, S.; Welch, I.; West, C. M.; Pritchard, S.
Abstract : Aims and Background . Patients in the United Kingdom with operable gastric and gastro-oesophageal junction (GOJ) tumours receive neoadjuvant chemotherapy. Our aim was to study the expression of thymidylate synthase (TS) enzyme in pre-treatment diagnostic biopsy specimens and investigate its clinical usefulness. Methods . A single-centre study was carried out in 45 patients with gastric and GOJ adenocarcinoma treated with neo-adjuvant chemotherapy according to the MAGIC protocol. TS expression was determined using immunohistochemistry. >10% tumour nuclei expression of TS was used as cut-off for positivity. Results . Forty-one (91%) of the 45 tumours expressed TS. There was no association between TS expression and lymph node status ( P = 0.80), histological response ( P = 0.30), and recurrence ( P = 0.55). On univariate analysis, only N-stage ( P = 0.02) and vascular invasion ( P = 0.04) were associated with a poor prognosis. Patients with negative tumour TS expression had better outcome than those with positive expression. The overall 5-year survival rate was 100% in the TS negative versus 56% in TS positive group, but the difference was not statistically significant ( P = 0.17). Conclusion . TS expression should be studied in a larger series of gastro-oesophageal cancers as a potential prognostic marker of prognosis to neo-adjuvant chemotherapy.